Общие подходы к проектированию специализированного программного комплекса решения задач оптимизации - Овчаренко, В. В. (НТУ "ХПИ", 2007)
The work is devoted to basic approaches for projecting and design of a specialized optimization program product. The basic requirements for developing system were stated. The design principles were developed. Structural elements was distinguished. The common scheme of interaction between structural elements in frames of computing cluster was elaborated. The sphere of problems for further product development was described.
Keywords: оптимизационные процедуры; методы оптимизации; кластерные подходы; средства кластеризации; GRID-технологии; базовые принципы